UNDERSTANDING UNMADA W.S.R TO SCHIZOPHRENIA - Wilson, *Nicy; MJ, Prashasth; Dr, Muralidhara (International Journal of Ayurveda and Pharma Research, 2018)
Manasa Vikara are considered as an abnormal mental condition characterised by impairment of mental functions. Acharyas have elaborated the importance of Manas at various places in the classics. According to Acharya Susruta Manas is regarded as Ahankarika, whereas Caraka Acharya mentions Manas is evolved from Khadini. Acharya Susruta considers Krodha, Shoka, Bhaya etc., as the Nidana of Manasa Vikara whereas Caraka Acharya mentions attachment towards undesired objects and loss of desired objects as the Karana for Manovikara. Unmada is the most elaborately dealt Manasa Vyadhi in Ayurveda. Acharyas have included a broad spectrum of psychiatric disorders under Unmada. Alpa Satwa individuals are considered to be more prone for such disorders. Even the definition of â€œHealthâ€ by WHO suggest mental well-being along with physical and social well-being. Once any disturbance occurs it in turn disturbs the normalcy which may affect the personality of an individual, a characteristic distortion of thinking, disturbed perception etc. Schizophrenia is such a disease characterised by disturbances in thought, verbal behaviour, perception, affect, motor behaviour and relationship to the external world.